Multilayer oriented composite structure high-efficiency broadband wave-absorbing material and preparation method thereof

CN122931334APending Publication Date: 2026-10-16SUZHOU BOTAO NEW MATERIALS TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611236027.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-14
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

该类常规方案在特定窄频段下能够满足基础吸波需求,但随着电子设备集成度提高和电磁环境日益复杂,其性能局限逐渐显现

Benefits of technology

三重梯度过渡层使磁粉取向、导电网络和硅烷覆盖状态沿厚度协同变化,减小层间电磁参数突变,兼顾电磁波入射、宽频衰减及层间稳定;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to a kind of multilayer orientation composite structure high-efficiency broadband wave-absorbing materials and preparation method thereof, the wave-absorbing material includes surface layer magnetic orientation layer, intermediate triple gradient transition layer and bottom layer conductive loss layer in turn along electromagnetic wave incident direction;The surface layer magnetic orientation layer includes flaky soft magnetic powder arranged in magnetic orientation;The intermediate triple gradient transition layer includes at least three transition units arranged in turn and co-formed connection along the thickness direction, and the flaky soft magnetic powder in each transition unit includes high-silane coverage powder A and low-silane coverage powder B;From the side close to surface layer to the side close to bottom layer, the average orientation angle of flaky soft magnetic powder in each transition unit gradually decreases, the content of conductive filler gradually increases, and the mass ratio of high-silane coverage powder A and low-silane coverage powder B gradually decreases.The application is beneficial to improve the impedance matching of wave-absorbing material and improve the interlayer stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of electromagnetic functional composite materials, and in particular to a multi-layer oriented composite structure high-efficiency broadband microwave absorbing material and its preparation method. Background Technology

[0002] Electromagnetic absorbing materials, as core functional media for solving problems related to electromagnetic interference, electromagnetic compatibility, and radar stealth, have been widely applied in engineering fields such as communication base stations, vehicle-mounted radar, aerospace, and industrial electronic equipment. Currently, most common absorbing products employ single-layer mixed-doped or random-stacked structures, where magnetic absorbers and functional fillers are randomly dispersed within a single matrix layer and then molded as a whole for use. While these conventional solutions can meet basic absorbing requirements in specific narrow frequency bands, their performance limitations are becoming increasingly apparent as electronic equipment integration increases and electromagnetic environments become more complex.

[0003] In terms of impedance matching, homogeneous single-layer materials lack a gradual impedance transition from the air interface to the material interior. When electromagnetic waves are incident, abrupt changes in interface impedance easily cause strong reflections, making it difficult for some electromagnetic wave energy to penetrate the material interior. Regarding microscopic loss mechanisms, conventional mixing processes typically do not provide directional control of magnetic powders, resulting in random filler distribution and difficulty in fully coordinating magnetic response and interfacial polarization. Furthermore, the propagation and loss paths provided by a single homogeneous structure are relatively limited, making it difficult for low-frequency and high-frequency electromagnetic waves to attenuate synchronously. Some multilayer products rely on separate adhesives for step-by-step lamination, which can easily lead to additional dielectric interfaces and local defects between layers. During long-term service, delamination may also occur, affecting the continuity of interlayer electromagnetic parameters. Summary of the Invention

[0004] To improve impedance matching and interlayer stability of microwave absorbing materials, this application provides a high-efficiency broadband microwave absorbing material with a multilayer oriented composite structure and its preparation method.

[0005] In the first aspect, this application provides a multi-layered oriented composite structure high-efficiency broadband absorbing material, which adopts the following technical solution: A multi-layered oriented composite high-efficiency broadband microwave absorbing material comprises, sequentially along the electromagnetic wave incident direction, a surface magnetic orientation layer, an intermediate triple gradient transition layer, and a bottom conductive loss layer. The surface magnetic orientation layer contains sheet-like soft magnetic powder arranged in a magnetic orientation. The intermediate triple gradient transition layer comprises at least three transition units arranged sequentially along the thickness direction and co-formed together. The sheet-like soft magnetic powder in each transition unit comprises powder A with high silane coverage and powder B with low silane coverage. From the side closer to the surface to the side closer to the bottom layer: the average orientation angle of the sheet-like soft magnetic powder in each transition unit gradually decreases, and the content of conductive filler in each transition unit gradually increases; the mass ratio of powder A with high silane coverage to powder B with low silane coverage in each transition unit gradually decreases; the conductivity of the bottom conductive loss layer is higher than that of the adjacent transition unit; and the surface magnetic orientation layer, each transition unit, and the bottom conductive loss layer are co-formed together.

[0006] By adopting the above technical solution, a graded loss structure is formed along the electromagnetic wave propagation direction by the surface magnetic orientation layer, the middle triple gradient transition layer, and the bottom conductive loss layer. The directional arrangement of the surface sheet-like soft magnetic powder can form an anisotropic magnetic response that is different from that of the random filling layer. The middle layer gradually adjusts the magnetic response, interface polarization, interparticle electrical isolation, and conduction loss in different depth regions by gradually decreasing the magnetic powder orientation angle, gradually increasing the conductive filler content, and gradually changing the proportion of high and low silane covered powders. This allows the electromagnetic parameters of the surface magnetic region to gradually transition to the bottom high conductivity region. The higher conductivity structure of the bottom layer further dissipates the electromagnetic energy entering the material. The co-molded connection of each layer can reduce the additional dielectric interface and air gap formed by the independent adhesive layer and improve the interlayer stability, thus helping to balance electromagnetic wave entry, internal broadband attenuation, and long-term structural reliability.

[0007] Preferably, the intermediate triple gradient transition layer includes 3-5 transition units, and the high silane coverage powder A and the low silane coverage powder B are prepared using the same substrate and the same silane coupling agent but with different dosages. The surface silane coverage of the high silane coverage powder A is higher than that of the low silane coverage powder B.

[0008] By adopting the above technical solution and setting the intermediate layer into 3-5 transition units, a balance can be achieved between the degree of gradient refinement and manufacturing complexity. High silane coverage powder A and low silane coverage powder B use the same substrate and the same silane coupling agent, with different surface coverage states achieved only by varying the amount of coupling agent. This reduces the interference of differences in powder composition, particle size, and functional groups on performance evaluation. By changing the ratio of high silane coverage powder A to low silane coverage powder B, the dispersion of powder in the matrix, the powder-resin interface bonding, the electrical isolation distance between particles, and the polarization state of the heterogeneous interface can be gradually adjusted, enabling the chemical gradient to form a repeatable synergistic relationship with the orientation and conductivity gradients.

[0009] Preferably, the volume conductivity of each transition unit increases progressively from the side closer to the surface layer to the side closer to the bottom layer; the transition unit near the surface magnetic orientation layer does not form a through conductive network, while the transition unit near the bottom conductive loss layer forms a sparse conductive path, and the conductivity of the sparse conductive path is lower than that of the bottom conductive loss layer.

[0010] By adopting the above technical solution, the transition units near the incident side do not form a continuous conductive network, which avoids strong reflection of electromagnetic waves when they first enter the intermediate layer due to excessively high dielectric constant and conductivity. The volumetric conductivity is gradually increased along the thickness direction, and sparse conductive pathways are formed near the bottom layer, which gradually increases carrier migration, tunneling conduction, and interface polarization losses. The conductivity of the sparse network is still lower than that of the bottom conductive loss layer, allowing the intermediate layer to play a role in transitioning from a non-continuous state to a more complete graphene conductive network.

[0011] Preferably, there are resin interdiffusion regions between adjacent transition units, between transition units and the surface magnetic orientation layer, and between transition units and the underlying conductive loss layer.

[0012] By adopting the above technical solution, resin segments interdiffusion occurs between adjacent layers during the curing process, forming a continuous resin phase, which can reduce the new dielectric abrupt changes, bubbles, and local defects caused by independent adhesive layers.

[0013] Preferably, the conductive filler in the transition unit is selected from one or more of graphene, reduced graphene oxide, carbon nanotubes, and two-dimensional transition metal carbides, nitrides, or carbonitrides (MXene); the bottom conductive loss layer contains graphene.

[0014] By employing the above technical solutions, graphene, reduced graphene oxide, carbon nanotubes, and MXene can provide conductive pathways, polar sites, and heterogeneous interfaces in different dimensions. The conductive fillers are configured in a gradient according to their content within the transition units, which helps to enhance dipole polarization, interfacial polarization, and conduction loss while avoiding the premature formation of a highly reflective through-network. The bottom layer of graphene-containing conductive loss regions connects with the intermediate layer's conductive network, which extends the propagation and dissipation path of electromagnetic waves.

[0015] Preferably, the polymer matrix of the surface magnetic orientation layer, each transition unit and the bottom conductive loss layer are the same, and the polymer matrix is ​​selected from one of epoxy resin, polyurethane, silicone rubber and thermoplastic elastomer; the sheet-like soft magnetic powder is selected from one or more of sheet-like FeSiAl alloy powder, sheet-like FeSiCr alloy powder, sheet-like carbonyl iron powder and sheet-like permalloy powder.

[0016] By adopting the above technical solutions, epoxy resin, polyurethane, silicone rubber or thermoplastic elastomer can be selected according to flexibility, heat resistance and co-molding conditions; sheet-like FeSiAl, FeSiCr, carbonyl iron or permalloy powder has shape anisotropy and magnetic response, and its directional arrangement is beneficial to regulating the demagnetizing field, magnetic domain response and complex permeability dispersion.

[0017] Secondly, this application provides a method for preparing a multi-layered oriented composite high-efficiency broadband microwave absorbing material, employing the following technical solution: A method for preparing a multilayer oriented composite high-efficiency broadband microwave absorbing material includes the following steps: S1. Prepare powder A with high silane coverage and powder B with low silane coverage, with different surface silane coverage amounts; S2. Prepare a surface magnetic orientation slurry, at least three sets of transition slurries, and a bottom conductive loss slurry. According to the thickness construction order from the surface side to the bottom side, the proportion of high silane coverage powder A in each set of transition slurries decreases step by step, the proportion of low silane coverage powder B increases step by step, and the content of conductive filler increases step by step. S3. Form a film of the surface magnetic orientation paste and pre-shape it with magnetic orientation; S4. Coat each group of transition slurry in sequence, with the direction of the corresponding magnetic field changing step by step for each group, so that the average orientation angle of the sheet-like soft magnetic powder in each transition unit decreases step by step, and pre-shape it. S5. A bottom conductive loss layer is formed and connected by hot pressing to obtain a multi-layer oriented composite structure high-efficiency broadband absorbing material.

[0018] By employing the above technical solution, high-silane-coverage powder A and low-silane-coverage powder B are first prepared separately. Then, following the thickness construction sequence from the surface layer to the bottom layer, the proportions of powders A and B and the content of conductive fillers are gradually changed, which can fix the surface chemical state and conductive network at a predetermined depth. The surface layer and each transition slurry are oriented and pre-shaped under the corresponding magnetic field direction, which can reduce the risk of the already formed orientation re-rotation due to subsequent coating and magnetic field action, and make the orientation angle of the sheet magnetic powder change gradually along the thickness. Finally, the bottom conductive loss layer is formed and hot-pressed for co-molding, which can connect multiple functional units into a whole, giving the triple gradient a clear and repeatable process source.

[0019] Preferably, step S1 specifically includes the following steps: The flake-shaped soft magnetic powder is dispersed in a solvent, a silane coupling agent is added, and the mixture is stirred at 20-80℃ for 0.5-6 hours. After washing and drying, powder A with high silane coverage is obtained. Powder B with low silane coverage is produced using the same process, except that the amount of silane coupling agent used is lower than that of powder A with high silane coverage.

[0020] By adopting the above technical solution, high silane coverage powder A and low silane coverage powder B can form relatively high and low silane coverage states without changing the main composition and morphology of the magnetic powder, using the same flake-shaped soft magnetic powder, the same processing route and different coupling agent dosages.

[0021] Preferably, each group of transition slurry is applied sequentially in a state where it is not fully set, and a resin interdiffusion zone is formed between adjacent layers.

[0022] By adopting the above technical solution, each group of transition slurry is sequentially coated in a state that is not fully set. The previous layer can maintain the orientation of the formed magnetic powder and retain the resin chain flow and interfacial mixing ability.

[0023] In summary, this application includes at least one of the following beneficial technical effects: The triple gradient transition layer enables the magnetic powder orientation, conductive network and silane coverage state to change synergistically along the thickness, reducing abrupt changes in interlayer electromagnetic parameters and taking into account electromagnetic wave incidence, broadband attenuation and interlayer stability. The ratio of high and low silane-covered powders, combined with the gradient of conductive fillers, can adjust dispersion, interfacial polarization, and electrical isolation between particles, avoiding strong surface reflection caused by simply increasing the conductive phase; Layer-by-layer magnetic orientation, pre-formed overcoating, and hot-pressing co-molding form a resin interdiffusion zone, which can stabilize the triple gradient structure and improve interlayer reliability under bending and thermal cycling conditions. Detailed Implementation

[0024] The present application will be further described in detail below with reference to the embodiments: Raw material description: All raw materials in the examples are commercially available; the resin interdiffusion region can be observed by cross-sectional transmission electron microscopy (TEM) or confirmed by energy dispersive spectroscopy (EDS) line scanning, which shows that the resin phase at the interface of adjacent layers is continuous and without clear boundaries. Example 1

[0025] Preparation of high-efficiency broadband microwave absorbing materials with multi-layer oriented composite structures: S1. Take the same batch of sheet-like FeSiAl alloy powder, with an average sheet diameter of 30μm and an average thickness of 1.0μm, and divide it into two portions at a mass ratio of 1:1. The following instructions are based on 100g per portion, and the actual usage can be scaled up proportionally according to the formulation of each layer. Prepare 500mL of a mixed solvent of ethanol and deionized water in a volume ratio of 95:5, adjust the pH to 4.5 with acetic acid, and divide the mixed solvent into two equal portions. γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560) equivalent to 1.0% and 0.2% of the corresponding FeSiAl powder mass was added to two mixed solvents, respectively, and pre-hydrolyzed for 10 min to obtain high-volume pre-hydrolyzed solutions and low-volume pre-hydrolyzed solutions, respectively. One part of FeSiAl alloy powder was mixed with the high-volume pre-hydrolyzed solution and stirred at 500 rpm at 20 °C for 0.5 h. After the reaction, it was filtered, washed three times with ethanol, and vacuum dried at 60 °C for 4 h to obtain powder A with high silane coverage. Another part of FeSiAl alloy powder was mixed with the low-volume pre-hydrolyzed solution and stirred at 500 rpm at 20 °C for 0.5 h. After the reaction, it was filtered, washed three times with ethanol, and vacuum dried at 60 °C for 4 h to obtain powder B with low silane coverage. S2. Prepare the surface magnetic orientation slurry, three sets of transition slurries, and the bottom conductive loss slurry. Bisphenol A type epoxy resin E51 is used as the common polymer matrix for all layers. The following dosages are based on 100 parts by weight of E51 for each layer. For every 100 parts by weight of E51, 32 parts by weight of polyetheramine D230 and 8 parts by weight of benzyl glycidyl ether are added. An additional 0.8 parts by weight of polyether-modified siloxane dispersant is added to each layer. First, mix E51, benzyl glycidyl ether, and dispersant at 500 rpm for 5 minutes. Then, add magnetic powder and graphene in batches and disperse at 1200 rpm for 15 minutes. After adding D230, mix at 500 rpm for 3 minutes and then vacuum degas for 5 minutes. There are three transition units, T1, T2, and T3: The surface magnetic alignment layer contains 180 parts of high-silane-coverage powder A, 0 parts of low-silane-coverage powder B, and 0 parts of conductive filler, with a forming thickness of 0.30 mm; T1 contains 160 parts of magnetic powder (A:B = 80:20) and 0.2 parts of graphene, with a forming thickness of 0.25 mm; T2 contains 140 parts of magnetic powder (A:B = 50:50) and 0.6 parts of graphene, with a forming thickness of 0.25 mm; T3 contains 120 parts of magnetic powder (A:B = 20:80) and 1.0 part of graphene, with a forming thickness of 0.25 mm; the bottom conductive loss layer contains 6.0 parts of graphene, with a forming thickness of 0.30 mm. S3. Apply the surface slurry onto the release film, and control the wet film thickness to 0.30 mm after curing; orient for 3 minutes under the conditions of magnetic induction intensity of 0.35T and magnetic field direction with an angle of 85° with the surface layer, and pre-form at 60℃ for 5 minutes. S4. When the surface layer remains non-flowing and still viscous, apply T1, T2, and T3 slurries sequentially. After each layer is applied, align it for 3 minutes in a 0.35T magnetic field at angles of 70°, 40°, and 10° to the layer, and then pre-set it at 60°C for 4 minutes. S5. Apply the bottom conductive loss slurry to T3, then place all layers in a flat hot press and hot press at 80℃ and 2.0MPa for 60 minutes, then raise the temperature to 100℃ and hold for 60 minutes. After cooling to below 40℃, release the pressure to obtain a multi-layer oriented composite structure microwave absorbing material with a total thickness of about 1.35mm. Example 2

[0026] Preparation of high-efficiency broadband microwave absorbing materials with multi-layer oriented composite structures: S1. Mix flake FeSiCr alloy powder and flake permalloy powder at a mass ratio of 70:30 to obtain composite soft magnetic powder with an average flake diameter of 30-45 μm and an average thickness of 1.0-1.5 μm. Divide the powder into two portions at a mass ratio of 1:1. The following instructions are based on 100g per portion; the actual dosage can be scaled up proportionally according to the formulation of each layer. Prepare 500mL of a mixed solvent of isopropanol and deionized water at a volume ratio of 90:10. Adjust the pH to 4.2 with acetic acid and divide the mixed solvent into two equal portions. Add γ-methacryloyloxypropyltrimethoxysilane (KH570) equivalent to 5.0% and 0.5% of the corresponding composite soft magnetic powder mass to the two portions of mixed solvent, respectively, and pre-hydrolyze for 10 min. Add the two portions of composite soft magnetic powder to the corresponding pre-hydrolyzed solutions and react under reflux and condensation conditions at 80℃ and 400rpm for 6 h. After the reaction, the powders were filtered, washed three times with isopropanol, and dried under vacuum at 70°C for 6 hours to obtain powder A with high silane coverage and powder B with low silane coverage. S2. Prepare the surface magnetic orientation slurry, transition slurry, and bottom conductive loss slurry. Addition-type liquid silicone rubber is used as the common polymer matrix for all layers. Components A and B are mixed at a mass ratio of 1:1, based on 100 parts by mass of mixed silicone rubber. 0.5 parts by mass of a siloxane dispersant is added to each layer. Along the thickness direction, the proportion of high silane coverage powder A in each transition slurry group gradually decreases, the proportion of low silane coverage powder B gradually increases, and the content of conductive filler gradually increases. First, the conductive filler is dispersed in a planetary mixer at 800 rpm for 10 min, then powders A and B are added, mixed at 1000 rpm for 15 min, and then vacuum degassed for 8 min. There are five transition units: T1, T2, T3, T4, and T5. In the surface magnetic alignment layer, there are 220 parts of high-silane coverage powder A, 0 parts of low-silane coverage powder B, and 0 parts of conductive filler. The target average orientation angle is 90°, and the forming thickness is 0.35 mm. In T1, the total magnetic powder content is 200 parts, A:B = 90:10, and 0.2 parts of a composite of reduced graphene oxide and pre-prepared Ti3C2Tx MXene (mass ratio 2:1) are present. The target average orientation angle is 75°, and the forming thickness is 0.20 mm. In T2, the total magnetic powder content is 180 parts, A:B = 70:30, and the composite of reduced graphene oxide and pre-prepared Ti3C2Tx MXene is present. The first layer contains 0.6 parts of MXene composite, with a target average orientation angle of 60° and a molding thickness of 0.20 mm; the second layer contains 160 parts of magnetic powder, with an A:B ratio of 50:50, 1.0 part of reduced graphene oxide and pre-prepared Ti3C2TxMXene composite, a target average orientation angle of 45°, and a molding thickness of 0.20 mm; the third layer contains 140 parts of magnetic powder, with an A:B ratio of 30:70, 1.4 parts of reduced graphene oxide and pre-prepared Ti3C2TxMXene composite, a target average orientation angle of 25°, and a molding thickness of 0.20 mm; the fourth layer contains 120 parts of magnetic powder, with an A:B ratio of 10:90, 1.8 parts of reduced graphene oxide and pre-prepared Ti3C2TxMXene composite, a target average orientation angle of 5°, and a molding thickness of 0.20 mm; the bottom conductive loss layer contains graphene and pre-prepared Ti3C2Tx... 9.0 parts of MXene compound (mass ratio 5:1), molding thickness 0.35 mm; The conductive filler content in T1 is the lowest, and no through conductive network is formed; the conductive filler content in T5 is 1.8 parts, forming a sparse conductive network composed of contact and tunneling between conductive filler particles, and the volume conductivity of T5 is lower than that of the bottom conductive loss layer.

[0027] S3. Apply the surface slurry onto the release film, and control the wet film thickness to 0.35 mm after curing; orient it for 2 minutes under the conditions of magnetic induction intensity of 0.45T and magnetic field direction with an angle of 90° with the surface layer, and pre-form it at 80℃ for 90 seconds. S4. While the surface remains non-flowing and still viscous, sequentially apply slurries T1, T2, T3, T4, and T5. For each layer, align it for 2 minutes in a 0.45T magnetic field at angles of 75°, 60°, 45°, 25°, and 5° to the surface layer, respectively, and then pre-set at 80°C for 60 seconds. The transition slurries are applied sequentially in an incompletely set state, and adjacent layers form resin interdiffusion zones during the subsequent co-forming process. S5. Apply the bottom conductive loss slurry to T5, then place all layers in a flat hot press and hot press at 120℃ and 1.5MPa for 20 minutes, then post-treat at 150℃ for 60 minutes. After cooling to room temperature, release the pressure to obtain a multi-layer oriented composite structure microwave absorbing material with a surface magnetic orientation layer, each transition unit and the bottom conductive loss layer co-formed and connected. Resin interdiffusion zones are formed between adjacent layers, with a total thickness of about 1.70mm. Example 3

[0028] Preparation of high-efficiency broadband microwave absorbing materials with multi-layer oriented composite structures: S1. Take the same batch of flake-shaped carbonyl iron powder, with an average flake diameter of 20-30 μm and an average thickness of 0.6-1.0 μm, and divide it into two portions at a mass ratio of 1:1; the following instructions are based on 100g per portion, and the actual usage can be scaled up proportionally according to the formulation of each layer. Prepare 500 mL of a mixed solvent of ethanol and deionized water in a volume ratio of 90:10, adjust the pH to 4.8 with acetic acid, and divide the mixed solvent into two equal portions. Add γ-aminopropyltriethoxysilane (KH550) equivalent to 3.0% and 0.3% of the corresponding carbonyl iron powder mass to the two portions of mixed solvent, respectively, and pre-hydrolyze for 15 min; add the two portions of carbonyl iron powder to the corresponding pre-hydrolyzed solutions, and stir at 500 rpm for 3 h at 50 °C. After the reaction, filter, wash three times with ethanol, and vacuum dry at 60 °C for 5 h to obtain powder A with high silane coverage and powder B with low silane coverage. S2. Prepare the surface magnetic orientation slurry, transition slurry, and bottom conductive loss slurry. Polyether-type thermoplastic polyurethane elastomer is used as the common polymer matrix for all layers. It is dissolved in a mixed solvent of N,N-dimethylformamide and butanone in a 1:1 volume ratio to prepare a matrix solution with a solid content of 20%, based on 100 parts by weight of polyurethane solids. 0.8 parts by weight of polyurethane dispersant are added to each layer. Along the thickness direction, the proportion of high silane coverage powder A in each group of transition slurries gradually decreases, the proportion of low silane coverage powder B gradually increases, and the content of conductive filler gradually increases. First, graphene and multi-walled carbon nanotubes are added to part of the matrix solution and dispersed at 1500 rpm for 20 min. Then, powders A and B and the remaining matrix solution are added, mixed at 800 rpm for 15 min, and vacuum degassed for 10 min. There are four transition units: T1, T2, T3, and T4. The surface magnetic alignment layer contains 200 parts of high-silane-coverage powder A, 0 parts of low-silane-coverage powder B, and 0 parts of conductive filler. The target average orientation angle is 85°, and the forming thickness is 0.30 mm. T1 contains 180 parts of magnetic powder, A:B = 85:15, and 0.25 parts of a graphene and multi-walled carbon nanotube composite (mass ratio 4:1). The target average orientation angle is 70°, and the forming thickness is 0.25 mm. T2 contains 160 parts of magnetic powder, A:B = 60:40, and 0 parts of the graphene and multi-walled carbon nanotube composite. 70 parts, target average orientation angle 50°, forming thickness 0.25mm; T3 contains 140 parts of magnetic powder, A:B=35:65, 1.15 parts of graphene and multi-walled carbon nanotube composite, target average orientation angle 25°, forming thickness 0.25mm; T4 contains 120 parts of magnetic powder, A:B=15:85, 1.60 parts of graphene and multi-walled carbon nanotube composite, target average orientation angle 5°, forming thickness 0.25mm; the bottom conductive loss layer contains 7.0 parts of graphene and multi-walled carbon nanotube composite (mass ratio 9:1), forming thickness 0.30mm; T1 has the lowest content of conductive filler and does not form a through conductive network; T4 has a content of 1.60 parts of conductive filler and forms a sparse conductive network composed of contact and tunneling between conductive filler particles, and the volume conductivity of T4 is lower than that of the bottom conductive loss layer. S3. Apply the surface slurry onto the release film, and control the wet film thickness to 0.30 mm after curing; orient for 3 minutes under the conditions of magnetic induction intensity of 0.40T and magnetic field direction with an angle of 85° with the surface layer, and pre-set for 5 minutes under 60℃ hot air conditions. S4. While the surface layer remains non-flowing and still has a hot tack, sequentially apply slurries T1, T2, T3, and T4. For each layer, align it for 3 minutes in a 0.40T magnetic field at angles of 70°, 50°, 25°, and 5° to the layer, respectively, and then pre-set at 60°C for 4 minutes. The transition slurries are applied sequentially in an incompletely set state, and adjacent layers form resin interdiffusion zones during the subsequent co-forming process. S5. Apply the bottom conductive loss slurry to T4. After the interlayer interface has completed limited intermixing, vacuum dry all layers at 80°C until the mass is constant to reduce the risk of bubbles caused by DMF and methyl ethyl ketone residue. Then place it in a flat plate hot press and hot press at 150°C and 2.0MPa for 10 minutes. Cool to below 60°C while maintaining the pressure and then release the pressure to obtain a multi-layer oriented composite structure microwave absorbing material with co-formed connection between the surface magnetic orientation layer, each transition unit and the bottom conductive loss layer. Resin interdiffusion zone is formed between adjacent layers, with a total thickness of about 1.60mm. Example 4

[0029] Example 4 is based on Example 3. The difference between Example 4 and Example 3 is that in Example 4, the surface layer, T1-T4 and the bottom layer are completely dried, and then an acrylic adhesive film with a thickness of 0.03 mm is set between the five adjacent interfaces for hot pressing and lamination. At the same time, the thickness of each functional layer is reduced proportionally so that the total thickness of the sample after including the adhesive film is still about 1.60 mm, and the total areal density of each functional component is consistent with that of Example 3. Example 5

[0030] Example 5 is based on Example 3. The difference between Example 5 and Example 3 is that in Example 5, the low silane coverage powder B is replaced with the same batch of untreated flake carbonyl iron powder B0. Example 6

[0031] Example 6 is based on Example 3. The difference between Example 6 and Example 3 is that the amount of graphene and multi-walled carbon nanotube composite in T1, T2, T3 and T4 in Example 6 is adjusted to 2.0, 2.2, 2.4 and 2.6 parts respectively, maintaining a stepwise increase. Example 7

[0032] Example 7 is based on Example 3. The difference between Example 7 and Example 3 is that the amount of conductive filler in T1, T2, T3 and T4 in Example 7 is adjusted to 0.05, 0.10, 0.15 and 0.20 parts respectively, while still maintaining the stepwise increase. Example 8

[0033] Example 8 is based on Example 3. The difference between Example 8 and Example 3 is that in Example 8, after each layer is formed, it is dried at 60°C until the surface is non-sticky and the quality is constant before the next layer is coated. Example 9

[0034] Example 9 is based on Example 3. The difference between Example 9 and Example 3 is that in Example 9, all the graphene and multi-walled carbon nanotube composites in T1-T4 are replaced with conventional conductive carbon black by the same mass. Example 10

[0035] Example 10 is based on Example 3. The difference between Example 10 and Example 3 is that in Example 10, 7.0 parts of the bottom graphene and multi-walled carbon nanotube composite are replaced with 7.0 parts of conductive carbon black. Example 11

[0036] Example 11 is based on Example 3. The difference between Example 11 and Example 3 is that in Example 11, T3, T4 and the bottom layer are replaced with the addition-type liquid silicone rubber matrix described in Example 2. The silicone rubber components A and B are mixed in a mass ratio of 1:1. The magnetic powder, A:B ratio, conductive filler and molding thickness in T3 and T4 are still the same as in Example 3. After T3 and T4 are coated, they are pre-molded at 80°C for 60s, and finally hot-pressed at 120°C and 1.5MPa for 20min, and then post-treated at 150°C for 60min. Example 12

[0037] Example 12 is based on Example 3. The difference between Example 12 and Example 3 is that in Example 12, the magnetic powder, conductive filler and TPU matrix used in the surface layer, T1-T4 and the bottom layer are combined, while keeping the total dry basis amount, total areal density and total thickness of magnetic powder, conductive filler and TPU unchanged, and are mixed into a homogeneous slurry in one step; the slurry is coated into a single layer film with a total thickness of about 1.60 mm, oriented under the condition that the magnetic field direction is at an angle of 37.5° with the layer, and then hot-pressed at 150°C and 2.0 MPa for 10 min. Example 13

[0038] Example 13 is based on Example 3. The difference between Example 13 and Example 3 is that no magnetic field is applied or orientation locking is performed during the coating of the surface layer and the T1-T4 process in Example 13. After the T4 coating is completed, a magnetic field of 0.40T with an angle of 37.5° to the surface layer is uniformly applied to the entire layer for 3 minutes, and then the bottom layer is formed and hot-pressed. Example 14

[0039] Example 14 is based on Example 3. The difference between Example 14 and Example 3 is that in Example 14, the surface layer and T1-T4 are not pre-formed at 60°C after coating. The next layer is coated immediately while the previous layer is still obviously fluid. Finally, the bottom layer is directly formed and hot-pressed for co-forming.

[0040] Comparative Example 1 Comparative Example 1 is based on Example 3. In Comparative Example 1, T1, T2, T3 and T4 are all oriented under the condition that the magnetic field direction makes an angle of 37.5° with the plane.

[0041] Comparative Example 2 Comparative Example 2 is based on Example 3. In Comparative Example 2, the amount of graphene and multi-walled carbon nanotube composite in T1-T4 is 0.925 parts.

[0042] Comparative Example 3 Comparative Example 3 is based on Example 3. In Comparative Example 3, the mass ratio of high silane coverage powder A to low silane coverage powder B in T1-T4 is 52.7:47.3.

[0043] Comparative Example 4 Comparative Example 4 is based on Example 3. In Comparative Example 4, T1-T4 are combined into a homogeneous intermediate layer with a thickness of 1.00 mm, wherein the total amount of magnetic powder is 150 parts, A:B=52.7:47.3, conductive filler is 0.925 parts, and the magnetic field direction is at an angle of 37.5° with the layer.

[0044] Performance testing The following performance tests were performed on the samples of Examples 1-14 and Comparative Examples 1-4: (1) Waveguide testing Using GB / T 32596-2016 and GB / T 35679-2017 as testing references, and based on the waveguide cross-sectional dimensions of different bands from 2 to 18 GHz, samples matching the waveguide's inner cross-section and without edge notches were cut from each material. Each sample retained its actual forming thickness, and a vector network analyzer was used to complete the through-reflection-transmission calibration. A metal short-circuit plate was placed on the back of the sample, and the reflection coefficient S11 was measured. The reflection loss is calculated as RL(f) = 20lg|S11(f)|; the most negative RL value of each sample in the 2-18GHz range is recorded as RLmin; the sum of the widths of the continuous frequency intervals corresponding to RL≤-10dB is recorded as the effective absorption bandwidth EAB; each sample is tested 3 times, the average value is taken, and the test results are filled in Table 1; (2) Interlayer T-peel strength Using GB / T 2791-1995 as the test reference, T-peeling was performed on a universal testing machine at a speed of 100 mm / min. The average force in the stable peeling range was divided by the sample width, with the unit being N / mm. Each sample was tested 3 times, and the average value was taken. The test results were then recorded in Table 1. (3) Effective absorption bandwidth retention rate after temperature cycling Using GB / T 2423.22-2012 as the test reference, the sample was cycled between -40℃ and 100℃, with each temperature point held for 30 minutes and the transition time not exceeding 5 minutes. A total of 100 cycles were performed. After the test, the sample was allowed to recover for 24 hours at 23±2℃ and 50±5% relative humidity. The EAB was then measured again using the aforementioned method, and the retention rate was calculated. Each sample was tested 3 times, and the average value was taken. The test results were recorded in Table 1.

[0045] Table 1 Performance test results of Examples 1-14 and Comparative Examples 1-4

[0046] As shown in Table 1, the RLmin of Examples 1-3 reached -38.7dB, -40.9dB and -45.3dB respectively, and the EAB was 6.5-7.8GHz. This indicates that epoxy, silicone rubber and TPU matrices can all form good broadband absorption through hierarchical orientation, increasing conductive phase and changing silane coverage ratio.

[0047] Example 4 uses an independent acrylate interlayer. The acrylic adhesive layer is a polymer layer with low cross-linking density and a modulus lower than that of the epoxy resin matrix. Under stress, it preferentially deforms and breaks inside the adhesive layer. Moreover, the thermal expansion and contraction during thermal cycling is inconsistent with that of the epoxy layer, resulting in interlayer stress.

[0048] In Example 5, no silane coupling agent was added to powder B, making the exposed magnetic powder more prone to agglomeration, oxidation, and reduced interfacial bonding with the resin.

[0049] The conductive fillers in Examples 6 and 7 are not within the scope defined in this application. The conductive filler in Example 6 is too high, and the front area approaches the conductive continuity state earlier, resulting in poor impedance matching. The conductive filler in Example 7 is insufficient, resulting in low front-end reflection, but insufficient internal polarization and conduction loss.

[0050] In Example 8, each layer was completely dried before being overcoated, which restricted the interdiffusion of resin segments and reduced performance.

[0051] In Example 9, all graphene and multi-walled carbon nanotubes were replaced with conductive carbon black. Although conductive carbon black can form conductive losses, it lacks two-dimensional sheets, one-dimensional bridging, and the multi-scale heterogeneous interfaces it forms, resulting in a decrease in performance.

[0052] In Example 10, the bottom layer of graphene and multi-walled carbon nanotubes was replaced with conductive carbon black. The conductivity was significantly lower than that of the graphene bottom layer, so it could not form an effective "high conductivity and strong attenuation shielding layer" function. Moreover, the conductivity of the bottom layer was small compared with T4, and the end-loop loss mechanism failed.

[0053] Example 11 uses a layer-by-layer pre-formed structure in the lower part. The chemical composition, crosslinking density, and curing temperature window of different polymer matrices are different. TPU and silicone rubber cannot form covalent bonds or molecular chain entanglements at the interface and rely only on physical contact bonding, resulting in a decrease in interfacial bonding strength.

[0054] Example 12 combines all components into a single-layer homogeneous film, representing the difficulty of achieving both incident matching and internal attenuation in traditional homogeneous mixed structures.

[0055] In Example 13, a 37.5° magnetic field was uniformly applied after all layers were coated. After uniform application, the orientation was easily limited by the viscosity of different layers and the existing structure, resulting in poor actual orientation uniformity and gradient controllability.

[0056] Example 14 does not perform layer-by-layer pre-forming, and the slurry is more thoroughly mixed, so the peel strength is actually higher. However, the next layer is coated before the previous layer reaches a semi-solid state, and the two slurries are severely mixed and interleaved. The A and B ratios, conductive filler content and orientation state between each layer are partially averaged, and the pre-set gradient structure is destroyed.

[0057] In Comparative Example 1, the average orientation angle of all layers is the same and there is no gradual change. The anisotropic magnetic responses of each layer completely overlap in the same frequency band, making it impossible to achieve the broadband superposition effect of multi-band magnetic loss.

[0058] In Comparative Example 2, the conductive filler content in T1-T4 was 0.925 parts, and the conductivity of each layer was consistent, making it impossible to form a conductivity gradient transition from a non-connected, sparse network to a highly conductive bottom layer.

[0059] In Comparative Example 3, the mass ratio of powder A with high silane coverage to powder B with low silane coverage was 48.75:51.25. The chemical state of each layer was consistent, and a silane coverage gradient could not be formed.

[0060] Comparative Example 4 merges the four transition units into a homogeneous intermediate layer. After losing the hierarchical relationship in the thickness direction, it is difficult to form a smooth magnetic-dielectric transition.

[0061] This specific embodiment is merely an explanation of this application and is not intended to limit it. Based on the above description, those skilled in the art can make various changes and modifications without departing from the technical concept of this application. The technical scope of this application is not limited to the contents of the specification but must be determined according to the scope of the claims.

Claims

1. A multi-layered oriented composite structure high-efficiency broadband microwave absorbing material, characterized in that: The structure comprises, sequentially along the electromagnetic wave incident direction, a surface magnetic alignment layer, an intermediate triple gradient transition layer, and a bottom conductive loss layer. The surface magnetic alignment layer contains sheet-like soft magnetic powder arranged in a magnetic orientation. The intermediate triple gradient transition layer comprises at least three transition units arranged sequentially along the thickness direction and co-formed together. The sheet-like soft magnetic powder in each transition unit contains powder A with high silane coverage and powder B with low silane coverage. From the side closer to the surface to the side closer to the bottom layer: the average orientation angle of the sheet-like soft magnetic powder in each transition unit gradually decreases, and the content of conductive filler in each transition unit gradually increases. The mass ratio of powder A with high silane coverage to powder B with low silane coverage in each transition unit gradually decreases. The conductivity of the bottom conductive loss layer is higher than that of the adjacent transition unit. The surface magnetic alignment layer, each transition unit, and the bottom conductive loss layer are co-formed together.

2. The high-efficiency broadband microwave absorbing material with a multi-layered oriented composite structure according to claim 1, characterized in that: The intermediate triple gradient transition layer includes 3-5 transition units. The high silane coverage powder A and the low silane coverage powder B are prepared using the same substrate and the same silane coupling agent but with different dosages. The surface silane coverage of the high silane coverage powder A is higher than that of the low silane coverage powder B.

3. The high-efficiency broadband microwave absorbing material with a multi-layered oriented composite structure according to claim 2, characterized in that: From the side closer to the surface to the side closer to the bottom layer, the volume conductivity of each transition unit increases step by step; the transition unit near the surface magnetic orientation layer does not form a through conductive network, while the transition unit near the bottom conductive loss layer forms a sparse conductive path, and the conductivity of the sparse conductive path is lower than that of the bottom conductive loss layer.

4. The high-efficiency broadband microwave absorbing material with a multi-layered oriented composite structure according to claim 2, characterized in that: There are resin interdiffusion regions between adjacent transition units, between transition units and the surface magnetic orientation layer, and between transition units and the underlying conductive loss layer.

5. The high-efficiency broadband absorbing material with a multi-layered oriented composite structure according to claim 4, characterized in that: The conductive filler in the transition unit is selected from one or more of graphene, reduced graphene oxide, carbon nanotubes, and two-dimensional transition metal carbides, nitrides, or carbonitrides (MXene); the bottom conductive loss layer contains graphene.

6. The high-efficiency broadband microwave absorbing material with a multi-layer oriented composite structure according to claim 5, characterized in that: The surface magnetic orientation layer, each transition unit, and the bottom conductive loss layer have the same polymer matrix, which is selected from epoxy resin, polyurethane, silicone rubber, and thermoplastic elastomer; the sheet-like soft magnetic powder is selected from one or more of sheet-like FeSiAl alloy powder, sheet-like FeSiCr alloy powder, sheet-like carbonyl iron powder, and sheet-like permalloy powder.

7. A method for preparing a high-efficiency broadband microwave absorbing material with a multi-layer oriented composite structure as described in any one of claims 1-6, characterized in that: Includes the following steps: S1. Prepare powder A with high silane coverage and powder B with low silane coverage, with different surface silane coverage amounts; S2. Prepare a surface magnetic orientation slurry, at least three sets of transition slurries, and a bottom conductive loss slurry. According to the thickness construction order from the surface side to the bottom side, the proportion of high silane coverage powder A in each set of transition slurries decreases step by step, the proportion of low silane coverage powder B increases step by step, and the content of conductive filler increases step by step. S3. Form a film of the surface magnetic orientation paste and pre-shape it with magnetic orientation; S4. Coat each group of transition slurry in sequence, with the direction of the corresponding magnetic field changing step by step for each group, so that the average orientation angle of the sheet-like soft magnetic powder in each transition unit decreases step by step, and pre-shape it. S5. A bottom conductive loss layer is formed and connected by hot pressing to obtain a multi-layer oriented composite structure high-efficiency broadband absorbing material.

8. The method for preparing a multi-layered oriented composite high-efficiency broadband absorbing material according to claim 7, characterized in that: Step S1 specifically includes the following steps: The flake-shaped soft magnetic powder is dispersed in a solvent, a silane coupling agent is added, and the mixture is stirred at 20-80℃ for 0.5-6 hours. After washing and drying, powder A with high silane coverage is obtained. Powder B with low silane coverage is produced using the same process, except that the amount of silane coupling agent used is lower than that of powder A with high silane coverage.

9. The method for preparing a multi-layered oriented composite high-efficiency broadband absorbing material according to claim 7, characterized in that: Each group of transition slurry is applied sequentially in a state where it is not fully set, and resin interdiffusion zones are formed between adjacent layers.